Ureterovesical Opaque Densities after Ureterovesical Reflux Injection Therapy: Diagnostic and Therapeutic Dilemma - Akhavizadegan, Hamed (Medknow Publications & Media Pvt Ltd, 2014)
Primary vesicoureteral reflux can be treated by injection of a bulking agent into the wall of the ureterovesical junction. Over time, the bulking agent can get calcified. Radiological images of the area show findings that mimic those seen in ureterovesical junction calculi. In this report, we present the imaging findings of this phenomenon and discuss its challenging aspects.